Effects of Fabrication Technique on Tensile Properties of Fiber Reinforced Polymer - Pham, Thong; Hadi, M.; Youssef, J. (ASTM International, 2017)
This study investigated the effects of fabrication technique on the tensile properties of fiber reinforced polymer (FRP) flat coupon tests. A total of 20 FRP flat coupons were prepared by two different techniques, which were tested in tension until failure. The first technique of preparing the FRP coupons was based on the recommendation of ASTM D7565/D7565M-10, named the "Cutting Technique", while the second technique, named the "Folding Technique', was proposed by this study. Experimental results from this study indicated that preparing FRP coupons using the Cutting Technique resulted in a reduction in the tensile properties as compared to coupons prepared by the proposed Folding Technique. most notably, the tensile force per unit width obtained by the FRP flat coupons prepared using the Folding Techniques was up to 8% higher than that obtained by coupons prepared using the Cutting Technique. In addition, the effect of the % bending on the tensile properties was also studies. It was found that the % bending about the thickness plane was greater than that of the % bending about the width plane. Furthermore, the tensile properties of the FRP coupons were not sensitive to its % bending.